Duodenal and thyroid metastasis of hypernephroma resected 16 years earlier. - Badano Repetto, José L; Paperán, Juan; Perrone, Luis; Pizzoli, Adela (Cirugía del Uruguay, 1976)
A patient had a hypernephroma resected, but successive metastasis occurred over a period of 16 years in different organs. However this patient is still alive. Metachronological metastasis appeared at various intervals: thyroid, at 11 years, lung at 13 · years, duodenum at 16 years and thyroid again 17 years after nephrectomy . It should be noted that metastasis in the duodenum is extremely rare. Evolution was favourable as a result oi the association of different therapies.